Dominant conceptions about public space and socio-spatial fragmentation: Empirical analysis of the city of Mossoro (RN)-Brazil - Bender, Pablo Martin [UNESP] (Univ Nacl Centro Provincia Buenos Aires, Centro Investigaciones Geografica, 2022)
The 'dominant conceptions' related to 'public sphere' and public space' present in Habermas, Arendt, Sennett and Davis are analyzed, exposing their ideas, and the reflections of their main critics. It is argued that the conceptions elaborated by the cited authors are related to a consensual and inert vision of the public space, which prevents considering the possibility of insurgency or social change. Subsequently, we present elements of analysis that allow us to understand the public space from an alternative, dialectical, and creative perspective; located in the Latin-American reality, developing into the category of 'socio-spatial fragmentation', in the light of observations made during two fieldworks, which occurred in the middle city of Mossoro, in the Brazilian northeast. Our proposal allows us to consider the disputes and creative uses that are made no public space, mainly among the subordinate classes, and that allows us to reconsider the idea of `death' and `crise' of public space.
Keywords: Public sphere; Public space; Spatial dialectics; Middle city